Performance of Tuberose (Polianthes tuberosa L.) Cultivars in Goa - K Ramachandrudu (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2009)
Tuberose is one of the popular cut flowers in Goa and holds great potential for cultivation in the state. The experiment laid out in randomized block design (RBD) with four replications was conducted at ICAR Research Complex, Ela, Old Goa, during 2003-04 to evaluate the performance of five tuberose cultivars under local agroclimatic conditions. Results were significant among cultivars for all characters except bulb production/plant. Maximum plant height was observed in 'Prajwal' whereas, the minimum was observed in 'Shringar'. Among the cultivars, 'Mexican Single' was found to be early, while, 'Suvasini' and 'Prajwal' were late in flowering. Highest number of florets/spike was recorded in 'Suvasini', closely followed by 'Vaibhav'. The best performance for spike length, number of spikes/plant, number of bulbs/plant, bulb weight and bulb diameter was observed in Mexican Single.